Effects of Carbofuran on Lantana camara and its biocontrol agent, Teleonemia scrupulosa. Issue 8 (3rd August 2019) - Katembo, Naweji; Witkowski, Ed T.F.; Byrne, Marcus J.
ABSTRACT: This laboratory-based study sought to determine the efficacy of using carbofuran in an exclusion experiment aimed at assessing the impacts of biocontrol agents on Lantana camara L. (sensu lato) (Verbenaceae). Two separate experiments were conducted, the first one on insect-free plants, to determine the effects of carbofuran solely on plant growth; and the second one, on Teleonemia scrupulosa St å l (Hemiptera: Tingidae) infested plants, with the objective of determining the impact of carbofuran on this biocontrol agent, as well as its impacts on plant growth. Carbofuran granules (10% a.i.) were applied at 7 g/m 2 a.i. to the potting medium. It was found that carbofuran did not have a significant effect on plant growth. Total removal of T. scrupulosa from exclusion plants (carbofuran-treated plants) was not achieved; however the low level of leaf feeding lesions on those plants indicated that carbofuran had considerably reduced the insect's population density. Results from a bioassay showed 100% and 40% T. scrupulosa mortality on leaves collected from carbofuran-treated and control plants, respectively, within three weeks of exposure. Analysis of chemical residue levels in the leaf material revealed that carbofuran potency only persisted for about three weeks, and was detectable at trace levels (<0.1 mg/kg). It was therefore concluded that carbofuran was effective at reducing the population of T. scrupulosa on its host plant, but only briefly. Carbofuran should be applied at least once every three weeks or at a higher dosage in order to maintain a low insect population for the duration of an experiment or to achieve total exclusion. For better insect removal, one should consider combining carbofuran and foliar insecticides.